2014
DOI: 10.1371/journal.pone.0096770
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasma gondii Decreases the Reproductive Fitness in Mice

Abstract: Toxoplasma gondii is a common protozoan parasite that infects warm-blooded animals throughout the world, including mice and humans. During infection, both, the parasite and the host, utilize various mechanisms to maximize their own reproductive success. Mice and humans are both the intermediate hosts for Toxoplasma gondii, which forms specialized vacuoles containing reproductive cysts in the formers’ tissue. As half of the human population is infected, developing a disease called toxoplasmosis, along with an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 53 publications
2
34
0
Order By: Relevance
“…the deteriorated health of chronically infected hosts. -Hortova et al (2014) have demonstrated a direct relation between infection with T. gondii and a decreased male reproductive fitness in mice. They have observed significant differences in the reproductive parameters obtained from a detailed testicular histometric analysis and in DNA methylation pattern of the testicular epigenome between T. gondii-infected and T. gondii-free mice.…”
Section: Discussionmentioning
confidence: 99%
“…the deteriorated health of chronically infected hosts. -Hortova et al (2014) have demonstrated a direct relation between infection with T. gondii and a decreased male reproductive fitness in mice. They have observed significant differences in the reproductive parameters obtained from a detailed testicular histometric analysis and in DNA methylation pattern of the testicular epigenome between T. gondii-infected and T. gondii-free mice.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have characterized infections that lead to a reduction in various reproductive measurements, like gametogenesis (gamete development), fertility and parental care [ 3 ]. Decreased gametogenesis occurred in the northern cricket frog after antigenic stimulation [ 4 ], in mice exposed to Toxoplasma gondii [ 5 ], in cattle with viral diarrhoea [ 6 ] and pneumonia [ 7 ], in dogs with canine leishmaniasis [ 8 ], and in humans with Helicobacter pylori infection [ 9 ] and AIDS [ 10 , 11 ]. Decreased overall fertility has been reported in the insect Rhodnius prolixus when infected with Trypanosoma rangeli [ 12 ], and decreased parental care effort has been observed in blue tits [ 13 ], and in house sparrows as they combat infection [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we measured reproductive effort in P. corroboree and L. v. alpina experimentally infected with Bd. In males, we counted spermatogenesis stages, number of spermatic cysts and seminiferous tubule area as a proxy for reproductive effort [ 4 , 5 , 33 ]. In female L. v. alpina , we measured mass of the gonads, and counted developed eggs and total grossly visible cells inside the ovaries.…”
Section: Introductionmentioning
confidence: 99%
“…Dass et al found altered DNA methylation of the vasopressin receptor in the amygdala of chronically infected mice [50]. Altered methylation status of the promoters of spermatogenesis genes in infected testis was also observed [93]. This suggests that T. gondii is able to co-op host mechanisms of chromatin regulation.…”
Section: Epigenetic Changesmentioning
confidence: 99%